2013
DOI: 10.1016/j.engfracmech.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Design based on ductile–brittle transition temperature for API 5L X65 steel used for dense CO2 transport

Abstract: Abstract. Safe and reliable transport of dense CO 2 by pipes needs a careful choice of the constitutive pipe materials to prevent brittle crack propagation after ductile or brittle failure initiation. This unexpected phenomenon can occur after failure or leak promoted by external interferences. In this case, the rapid decompression of dense CO 2 into gas leads to a very low local temperature of about -80°C. To prevent risk of brittle fracture initiation and propagation, the material must remain ductile at this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…italicT0=italicT0.Tstress=0+aitalicTitalicstress,where α is a parameter that depends on the yield stress. A similar relation has been found for X65 pipe steel by Capelle et al between various transition temperatures T t ( T t , tensile , T 0 and T K 1/2 ) and critical effective T ‐stress ( T ef , c ). italicTitalict=italicTt.Tef,c=0+0.14italicTef,c…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…italicT0=italicT0.Tstress=0+aitalicTitalicstress,where α is a parameter that depends on the yield stress. A similar relation has been found for X65 pipe steel by Capelle et al between various transition temperatures T t ( T t , tensile , T 0 and T K 1/2 ) and critical effective T ‐stress ( T ef , c ). italicTitalict=italicTt.Tef,c=0+0.14italicTef,c…”
Section: Introductionsupporting
confidence: 85%
“…Charpy impact tests have been performed on API 5L X65 pipe steel with standard Charpy specimens at temperature range [−196 to 20 °C] . Plotting the fracture energy Kc V (J) temperature and fitting the data according to Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Ren 2 carried out tensile tests of a 420-MPa steel with temperature ranging from 0°C down to −90°C and found that the Lüders strain [3][4][5] increased as the temperature decreased. For most structural steels, as the temperature decreases continuously, the fracture behaviour will transform from ductile to brittle (DBT), [6][7][8][9][10][11][12] reducing the steels' ductility and fracture toughness. The DBT occurs when the temperature decreases down to the steel's DBT temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The yield strength and ultimate tensile strength of the X65 steel were obtained via relation to hardness [7] ( Y = 550 and u = 633 MPa), while the fracture toughness of 280 MPa √m was used [8].…”
Section: Introductionmentioning
confidence: 99%